2013
DOI: 10.1242/dev.096537
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor Nf2 limits expansion of the neural progenitor pool by inhibiting Yap/Taz transcriptional coactivators

Abstract: SUMMARYBrain development requires a precise balance between expansion of the neural progenitor pool and the production of postmitotic neurons and glia. Disruption of this equilibrium results in a myriad of structural abnormalities and disorders of the nervous system. The molecular mechanism that restricts neural progenitor expansion is poorly understood. Here we show that the tumor suppressor neurofibromatosis 2 (Nf2; merlin) limits the expansion of neural progenitor cells (NPCs) in the mammalian dorsal telenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 59 publications
12
83
0
Order By: Relevance
“…We examined Nf2 protein localization at E15.5, when pioneer axons reach the midline. As reported previously (Lavado et al, 2013), Nf2 localized at the apical region of NPCs, highlighting the ventricular surface (Fig. 1G, arrowhead).…”
Section: Nf2 Is Required For Corpus Callosum and Hippocampal Commissusupporting
confidence: 86%
See 2 more Smart Citations
“…We examined Nf2 protein localization at E15.5, when pioneer axons reach the midline. As reported previously (Lavado et al, 2013), Nf2 localized at the apical region of NPCs, highlighting the ventricular surface (Fig. 1G, arrowhead).…”
Section: Nf2 Is Required For Corpus Callosum and Hippocampal Commissusupporting
confidence: 86%
“…We previously found that deleting floxed alleles of Nf2 (Nf2 (Giovannini et al, 2000) with Emx1-cre, which is expressed in the dorsal telencephalon by E10.5 (Gorski et al, 2002), results in callosal agenesis (Lavado et al, 2013). Luxol Blue staining of adult brain sections to detect myelinated axons showed that, in Nf2 mutants (Nf2 F/F ;Emx1-Cre), the corpus callosum was absent along the rostrocaudal axis with few, if any, fibers crossing the midline (Fig.…”
Section: Nf2 Is Required For Corpus Callosum and Hippocampal Commissumentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with these previous studies. We are also aware of reports that YAP regulates neural progenitor cell numbers in the developing neural tube of chick and Xenopus embryos and the mouse hippocampus, as shown in YAP gain-or loss-of-function assays (Cao et al, 2008;Gee et al, 2011;Lavado et al, 2013;Piccolo et al, 2014). However, our results showed normal neocortical neurogenesis in culture and in P0-P1 Yap nestin -CKO mice (Figs 3, 5, 6 and S6).…”
Section: Discussionsupporting
confidence: 50%
“…Knockdown of FAT4 in the developing chick or mouse neural tube increases neural progenitor numbers in a YAP-dependent fashion (Cappello et al, 2013;Van Hateren et al, 2011). Additionally, NF2/Merlin has recently been shown to suppress mouse neural progenitor expansion by inhibiting TAZ/YAP activity (Lavado et al, 2013). How nuclear TAZ/YAP activity controls progenitor proliferation is poorly understood, but is likely to involve the activation of genes encoding cell cycle regulators, such as cyclin D1, and inhibition of pro-differentiation factors, such as NeuroM (Cao et al, 2008).…”
Section: Nervous Systemmentioning
confidence: 99%